Shikonin inhibits myeloid differentiation protein 2 to prevent LPS‐induced acute lung injury. (25th January 2018) - Zhang, Yali; Xu, Tingting; Pan, Zheer; Ge, Xiangting; Sun, Chuchu; Lu, Chun; Chen, Hongjin; Xiao, Zhongxiang; Zhang, Bing; Dai, Yuanrong; Liang, Guang
Abstract : Background and Purpose: Acute lung injury (ALI) is a challenging clinical syndrome, which manifests as an acute inflammatory response. Myeloid differentiation protein 2 (MD2) has an important role in mediating LPS‐induced inflammation. Currently, there are no effective molecular‐based therapies for ALI or viable biomarkers for predicting the severity of disease. Recent preclinical studies have shown that shikonin, a natural naphthoquinone, prevents LPS‐induced inflammation. However, little is known about the underlying mechanisms. Experimental Approach: The binding affinity of shikonin to MD2 was analysed using computer docking, surface plasmon resonance analysis andelisa . In vitro, the anti‐inflammatory effect and mechanism of shikonin were investigated throughelisa, real‐time quantitative reverse transcription PCR, Western blotting and immunoprecipitation assay. In vivo, lung injury was induced by intratracheal administration of LPS and assessed by changes in the histopathological and inflammatory markers. The underlying mechanisms were investigated by immunoprecipitation in lung tissue. Key Results: Shikonin directly bound to MD2 and interfered with the activation of toll‐like receptor 4 (TLR4) induced by LPS. In cultured macrophages, shikonin inhibited TLR4 signalling and pro‐inflammatory cytokine production. These effects were produced through suppression of key signalling proteins including the NF‐κB and the MAPK pathway. We also showed that shikonin inhibits MD2–TLR4 complex formation and reduces LPS‐induced inflammatory responses in a mouse model of ALI. Conclusions and Implications: Our studies have uncovered the mechanism underlying the biological activity of shikonin in ALI and suggest that the targeting of MD2 may prove to be beneficial as a treatment option for this condition.